1986
DOI: 10.4315/0362-028x-49.10.786
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Mold in Food by Enzyme-Linked Immunosorbent Assay

Abstract: Evaluation of the enzyme-linked immunosorbent assay (ELISA) for detecting a mold-specific, heat-stable and water-soluble antigen demonstrated the potential of the method for detecting molds in food products. The mold antigen, as produced by Penicillium spp. and Aspergillus spp., was present in all food samples containing aflatoxin B1. The amount of mold antigen present in the test samples was related in each case to the aflatoxin B1 content. Experiments done with samples artificially inoculated with mycotoxin-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0
2

Year Published

1988
1988
2003
2003

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(13 citation statements)
references
References 0 publications
0
11
0
2
Order By: Relevance
“…As the antigens are heatstable (3,4,22), the method still works if the yeasts have been killed, e.g. in pasteurized foods and fruit juices.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As the antigens are heatstable (3,4,22), the method still works if the yeasts have been killed, e.g. in pasteurized foods and fruit juices.…”
Section: Resultsmentioning
confidence: 99%
“…It was concluded that each mould genus produces its own characteristic antigen which in some cases is produced in common with a closely related genus. This property may become a valuable aid to fungal taxonomy and already finds a practical application in the detection of moulds in food (3)(4)(5). The yeast Candida albicans produces a mannan that can be detected by ELISA in the serum of candidiasis patients (6)(7)(8)(9).…”
mentioning
confidence: 99%
“…Notermans and Heuvelman (1985) used an ELISA method to detect Mucor racemosus, F. oxysporium , and P. verrucosum in fruits and vegetables. They also developed another ELISA method to detect the presence of Penicillium and Aspergillus species in cereals, fruit juices, and spices (Notermans et al ., 1986). There have been several reports using ELISA methods for mold detection in grains, such as rice, barley or wheat (Dewey et al ., 1992;Banks et al ., 1994;Lu et al ., 1995).…”
mentioning
confidence: 99%
“…Elles sont encore peu développées et utilisées essentiellement pour la détection des champignons contaminants de denrées alimentaires, et non pour leur quantification (Notermans et Heuvelman, 1985 ;Lin et al, 1986 ;Notermans et al, 1986 ;Kamphuis et al, 1989 ;Notermans et Kamphuis, 1990). La méthode développée par Frankland et al (1981), grâce à l'utilisation d'un antisérum conjugué à la f1uores- Sur les fromages expérimentaux de type camembert, nous avons pu observer que Geotrichum candidum se développe dès les premiers jours d'affinage, malgré l'effet inhibiteur du salage, avant que la croissance…”
Section: Joursunclassified
“…La première étape de notre travail a donc consisté à mettre au point une méthode d'estimation de la biomasse de Penicillium camemberti et de Geotrichum candidum en mélange, fiable, reproductible et simple à mettre en oeuvre. Il existe actuellement diverses techniques appliquées à la détection de champignons contaminants des denrées alimentaires (Frankland et Lindley, 1978 ;Cousin et al, 1984 ;Lin et Cousin, 1985 ;Noterrnans et Heuvelman, 1985 ;Lin et al, 1986 ;Notermans et al, 1986 ;Kamphuis et al, 1989 ;Notermans et Kamphuis, 1990). Ces techniques, le plus souvent immunologiques, ne sont pas quantitatives.…”
Section: Introductionunclassified